EASY TO BUILD REMOTE MEASUREMENT AND CONTROL - LUSTIG, František (Trends in education, 2012)
This paper presents an application software as a new general trend in technical education. The paper describes how it is easy to built remote laboratory using ISES-hardware kit and ISES WEB Control - software kit.
Keywords: remote laboratory; e-learning; internet; ISES kit.